Oral health status and treatment needs of asthmatic children aged 6 - 12 Years in Lucknow - Pramod Kumar Yadav; Sabyasachi Saha; Sanjay Singh; N D Gupta; Neha Agrawal; Kusum Bharti (Wolters Kluwer Medknow Publications, 2017)
Introduction: Asthma is a growing public health problem affecting over 300 million people worldwide. Asthmatic children have an altered immune response and a high tendency to mouth breathing especially during an episode of rhinitis or an attack thus predisposing them to serious oral health problems. Aim: This study aims to assess oral health status of asthmatic children aged 6-12. Materials and Methods: A cross-sectional study was conducted among 450 asthmatic children aged 6-12 years in Lucknow, asthmatic children were chosen from pediatric department of major hospitals. Gingival index (GI), oral hygiene index-simplified (OHI-S), and dentition status and treatment need of World Health Organization oral health survey pro forma (1997) were used to assess oral health status. ANOVA, Chi-square test, and descriptive statistics were carried out. SPSS 16 was used for the data analysis. Results: Mean dynamical mean-field theory (DMFT) was 2.98 ± 1.52 and 3.05 ± 1.60, mean GI score was 1.55 ± 0.52 and 1.53 ± 0.42 and mean OHI-S was 2.59 ± 0.68 and 2.48 ± 0.77 among the male and female asthmatic children. Conclusion: Female asthmatic children had higher mean DMFT score, but lower mean GI score and oral hygiene score than male children in comparison and also they had a compromised oral hygiene status.